Abdominal Obesity Increased Breast Cancer Risk - Rabeta Mohd Salleh,; Suzana Shahar,; Fatimah Arshad,; Ahmad Rohi Ghazali,; Normah Haron,; Nor Fadilah Rajab, (penerbit ukm, 2007)
A case-control study was carried out to examine the association between adiposity and body composition with risk of breast cancer among 71 newly diagnosed breast cancer cases and 138 controls. Anthropometric parameters included height, weight, waist and hip circumferences, fasting blood glucose and blood pressures were measured on the subjects. Body composition was measured using bioelectrical impedance analysis (Maltron BF906). Results showed that the mean body mass index (BMI) among cases were 26.0 ± 4.8 kb/m² and 25.3 ± 4.5 kg/m² for control group (p>0.05). A total of 71% of the cases and 40% of the control had abdominal obesity (waist circumference ≥ 80 cm) [OR = 3.4 (95% CI + 1.7-6.9)] (p<0.05). Pre menopausal women have four times higher risk [Adjusted odds ratio OR + 4.3 (95% CI = 1.8-10.3)]. Percent of body fat was slightly higher in cases (36.4 ± 4.7%) compared to controls (35.3 ± 4.4%) but the difference was not significant. The mean of fat free mass (FFM) in controls was 38.8 ± 5.7 kg in cases. A weak positive correlation was shown between age and BMI (r =0.179, p+ 0.010), waist circumference (r = 0.218, p = 0.002), waist hip ratio (WHR) (r = 0.233, p = 0.001) and percent body fat (r = 0.330, p = 0.000). In conclusion, abdominal obesity increased breast cancer risk, especially among premenopausal women. This type of obesity and percentage of body fat was also found to increase with age. It is essential for women to maintain a normal waist line through healthy lifestyle in order to reduce breast cancer risk.